Pengaruh Pop Culture Asing terhadap Narasi dan Estetika Film Indonesia Kontemporer - Nurul Anam; Shovi Yatul Istifadah (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This study examines the influence of foreign pop culture on the narrative and aesthetics of contemporary Indonesian films. In the era of globalization, Indonesian filmmakers face the challenge of adapting global elements while preserving local identity. This research employs a qualitative approach by analyzing several Indonesian films, such as Gundala, Yuni, and Impetigore, which exhibit a unique blend of global and local themes. The findings reveal that foreign pop culture plays a significant role in shaping modern and globally competitive narrative structures and visual aesthetics while maintaining Indonesian cultural values. However, the risk of cultural homogenization remains a challenge. With the right adaptation strategies, Indonesian films can strengthen their position as cultural representations that are both globally and locally relevant. This study aims to contribute to the development of the Indonesian film industry amidst the influence of cultural globalization.